2015
DOI: 10.1016/j.jsat.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Exercise On Depression and Anxiety Symptoms Among Abstinent Methamphetamine-Dependent Individuals in A Residential Treatment Setting

Abstract: Background This paper reports data from a study designed to determine the impact of an 8-week exercise program on depression and anxiety symptoms among newly abstinent methamphetamine (MA)-dependent individuals in residential treatment. Methods One hundred thirty-five MA-dependent individuals, newly enrolled in residential treatment, were randomly assigned to receive either a 3-times-per-week, 60-minute structured exercise program for 8 weeks (24 sessions) or an equivalent number of health education sessions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 31 publications
5
73
0
2
Order By: Relevance
“…Methamphetamine-dependent individuals report symptoms of depression and drug craving (Zorick et al, 2010). Results from the larger clinical trial in which all subjects included in this study were enrolled showed significant effects of the exercise regimen to improve symptoms of depression and anxiety (Rawson et al, 2015). The neuroimaging findings presented here suggest that exercise-induced increases in D2/D3 BP ND may contribute to these behavioral effects, but direct examination of this relationship in the small neuroimaging subsample failed to detect any significant associations between improvements in ratings of affect and changes in D2/D3 dopamine receptor BP ND .…”
Section: Discussionmentioning
confidence: 92%
“…Methamphetamine-dependent individuals report symptoms of depression and drug craving (Zorick et al, 2010). Results from the larger clinical trial in which all subjects included in this study were enrolled showed significant effects of the exercise regimen to improve symptoms of depression and anxiety (Rawson et al, 2015). The neuroimaging findings presented here suggest that exercise-induced increases in D2/D3 BP ND may contribute to these behavioral effects, but direct examination of this relationship in the small neuroimaging subsample failed to detect any significant associations between improvements in ratings of affect and changes in D2/D3 dopamine receptor BP ND .…”
Section: Discussionmentioning
confidence: 92%
“…In three methodologically robust RCTs, exercise therapy was found to yield significant improvement in methamphetamine withdrawal symptoms such as craving as well as accompanying symptoms such as anxiety and depression (16)(17)(18). Professionally led, structured exercise programs conduced several times a week, with varying intensity, were studied, as well as an exercise program conducted by the patients themselves.…”
Section: Further Treatmentsmentioning
confidence: 99%
“…The recommendation for the nutritional supplements is based mainly on their low risk, rather than on any robust evidence of benefit: in a placebo-controlled RCT involving 60 patients, depressive manifestations as measured on the Inventory of Depressive Symptomatology-Clinician Rating (IDS-C) fell from 38.8 and 37.8 points at baseline in the drug and placebo groups, respectively, to 26.2 and 33.1 points at the end of the study (p = 0.05) (21). Psychoeducation and exercise therapy have been found effective and should be offered (17,23).…”
Section: Depression and Bipolar Disordermentioning
confidence: 99%
“…8,9 Recent reports analyzing exercisebased programs piloted at drug abuse treatment facilities have also shown that engaging in a consistent exercise regimen reduces withdrawal symptoms, increases the likelihood of remaining abstinent and decreases craving. [10][11][12][13] In animals, several studies have shown that wheel and treadmill running reduce the reinforcing effects of cocaine, as well as cocaine seeking when the exercise option is contemporaneously available.…”
Section: Introductionmentioning
confidence: 99%
“…We also compared the effects of early or late exercise to the effects of access to a locked or unlocked wheel throughout abstinence (days [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. On the basis of the neurobiological data, 29,33,38 we predicted that exercise during early abstinence would cause a greater decrease in cocaine seeking as compared with exercise during late abstinence.…”
Section: Introductionmentioning
confidence: 99%